2013
DOI: 10.4028/www.scientific.net/kem.577-578.33
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Soil - Concrete Plate Interaction Test and Numerical Models

Abstract: State of stress in foundation structure is structure is significantly influenced by the contact stress course in the subsoil. At the Faculty of Civil Engineering VSB TU Ostrava testing device was constructed so that the phenomena could be experimentally investigated and compared with numerical models. The objective of this paper is also improving and developing the soil-structure interaction analysis based on the experimental results and finite element method (FEM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…From the graph it is observed that, as the thickness of the slab increases, the variations of the stresses decrease, evidenced by the reduction in the curvature, which shows the stiffness contribution of the slab with the action of the load, supported every time in better foundation resistance. It is also observed that from 350 MPa, the soil tends to have less stress influence, corroborating what was expressed by authors and institutions (Cajka, Burkovic, Buchta, & Fojtik, 2014;PCA, 1984;Yoder & Witczak, 1975), who point out that improvements of the support layer do not have a structural purpose, these layers are placed to reduce the effect of erosion and the rise of fine materials to the surface (pumping). However, the improvement of the properties of the foundation, contributes slightly to improve the behavior of the system, which is a factor to be taken into account in the obtaining of the work stresses, especially when the slab is thin.…”
Section: Supportsupporting
confidence: 84%
“…From the graph it is observed that, as the thickness of the slab increases, the variations of the stresses decrease, evidenced by the reduction in the curvature, which shows the stiffness contribution of the slab with the action of the load, supported every time in better foundation resistance. It is also observed that from 350 MPa, the soil tends to have less stress influence, corroborating what was expressed by authors and institutions (Cajka, Burkovic, Buchta, & Fojtik, 2014;PCA, 1984;Yoder & Witczak, 1975), who point out that improvements of the support layer do not have a structural purpose, these layers are placed to reduce the effect of erosion and the rise of fine materials to the surface (pumping). However, the improvement of the properties of the foundation, contributes slightly to improve the behavior of the system, which is a factor to be taken into account in the obtaining of the work stresses, especially when the slab is thin.…”
Section: Supportsupporting
confidence: 84%
“…In addition, experimental measurements of stress and subsidence in subsoil were also carried out by many researchers such as G.X. Mei et al 2005 [8], Cajka et al 2014 [9] and [10]. M. Mohyla et al 2017 [11] analyzed stress under foundation slab with a physical surface interface between foundation slab and the subsoil by experimental measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The values were compared and impacts of 3D numerical model parameters on final deformation and internal forces in the steel-fibre reinforced foundation slab were evaluated. Another experimental loading tests and their results are also described in [2,3,6,7,8,11,19,20,21].…”
Section: Introductionmentioning
confidence: 99%